ISLAM DAN STRUKTUR PEMERINTAHAN KESULTANAN TERNATE - Asmiah (JURNAL ILMU BUDAYA, 2023)
The Sultanate of Ternate is a traditional government institution, which is the center of life and religious order that has been lived by the people of Ternate for centuries. In the Kolano form, genealogical and territorial ties are factors of integration. Meanwhile, in the form of a Sultanate, Islam is an integration factor. Several problems that are the center of attention in this research are, (1). The entry and development of Islam in Ternate, (2). Religious institutions. (3). The role of Islam in government. In this research, several approaches will be used involving various disciplines. It is hoped that this research can provide an overview of religious life in the past, which is very useful for understanding religious life today. This kind of local history research is of course also useful for filling in the National History framework.